Determinasi Kepercayaan Publik Terhadap Pemerintah Desa Dalam Mendorong Partisipasi Politik Masyarakat Cianjur Selatan - Somanteri, Asep (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to examine the determinants of public trust in village government in encouraging community political participation in the South Cianjur region. The transformation of village governance after the reform era through Law Number 6 of 2014 has positioned villages as strategic arenas of local democracy; however, challenges related to transparency and low substantive participation remain significant issues in semi-peripheral rural areas.The research employed a quantitative approach using an explanatory research design through Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis involving 170 respondents. The results indicate that village government transparency has a positive and significant effect on public trust (H1) as well as on community political participation (H2). Public trust was also found to significantly influence the enhancement of citizens’ political participation (H3). Furthermore, public trust acts as a significant mediating variable that strengthens the indirect relationship between transparency and political participation (H4).These findings confirm that transparency constitutes a fundamental foundation for building social trust capital, capable of transforming participation patterns from transactional engagement into inclusive and sustainable participation. This study recommends that village governments strengthen information accessibility and institutional responsiveness to enhance governmental legitimacy at the local level.